Modified Blowfish Algorithm - Theda Flare Ginoy Quilala; Ariel M Sison; Ruji P Medina (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Cryptography guarantees security in communication through encryption. This paper proposed a modified Blowfish encryption that uses 128-bit block size and 128-bit key to comply with minimum requirements as an encryption standard. The modification retained the original structure for easy migration but utilized two S-boxes to save memory. A derivation was added to prevent symmetry.  The algorithm’s performance was evaluated using time, and avalanche. Upon testing, the modified blowfish is slower with key, encryption, and decryption average of 26.99ms, 1651.83ms, and 2765.04ms compared to blowfish with 21.65ms, 1297.76ms and 2176.59ms due to block size difference. Applying 128-bit block size increases security by decreasing the chances of having duplicate blocks that may leak information. The modified Blowfish is faster compared to Twofish with an encryption and decryption average time of 2418.08ms and 4002.70ms. The added derivation improved the avalanche of the modified blowfish.  Blowfish achieved 47.14% while modified Blowfish attained 52.86%.